Syncope in children and adolescents: a two-year experience at theDepartment of Paediatrics in Parma - Bo, I.; Carano, N.; Agnetti, A.; Tchana, et al., B. (Acta Biomedica Atenei Parmensis, 2009)
Background and aim of the work: Syncope occurs frequently in childhood and adolescence. It generally is benign, but may be a sign of pathology. The purpose of this study is to determine the incidence of syncope in children and adolescents in the Parma area, analyse the frequency of syncope due to cardiac, neurological or metabolic diseases, to identify a diagnostic procedure based on careful review, clinical features, and results of investigations. Methods: The records of 156 children (age 1 to 18 years, mean age 10.5), who were referred to the Paediatric Department for syncope were reviewed. Results: The incidence of syncope in the paediatric population of Parma during a 2-year period (2005-2006) resulted in 86.5/100.000 per year. The cause of syncope was discovered in 154/156 cases. Cardiovascular syncope was diagnosed in 121/156 cases (77.5%). Neurological syncope was diagnosed in 31/156 cases (20%), while metabolic syncope was diagnosed in 2/156 cases (1.25%). The most frequent type was the (benign) neurocardiogenic syncope, but 3 cases were due to arrhythmia, 9 cases were due to epilepsy, 1 case was due to subarachnoid hemorrage and 2 cases were due to hypoglicemia. Conclusions: Syncope frequently requires medical examination or admission to paediatric departments and, in the majority of cases, does not subtend serious diseases. Nevertheless, syncope always requires a complete medical evaluation in order to exclude underlying pathology. An electrocardiogram must complete the initial evaluation of all patients with syncope. Other investigations are required if clinical data and the ECG do not provide an etiological explanation of the episode.